Long-term quality of life assessment after excisional treatment for cervical dysplasia. (3rd October 2022) - Sparić, Radmila; Bukumirić, Zoran; Stefanović, Radomir; Tinelli, Andrea; Kostov, Stoyan; Watrowski, Rafał
Abstract: We evaluated factors influencing long-term health-related quality of life (HRQoL) after excisional treatments of low- and high grade squamous intraepithelial cervical lesions (SIL) in three groups of women ( n  = 160): nulliparas interested in reproduction (A), parous women interested in reproduction (B) and women without pregnancy desire (C). The HRQoL was assessed using the disease-specific FACIT-CD and the generic SF36v2 questionnaires. Anxiety and depression were evaluated by Beck's inventories. After median follow-up of 5 (2–18) years, FACIT-CD total score and the score for Emotional Well-Being (EWB) were significantly lower in group A. The total, EWB and REL (Relationships) scores of FACIT-CD were the highest in group B. Women operated for HSIL demonstrated lower REL quality in comparison to those with LSIL. Neither SF36v2 nor FACIT-CD total scores differed in relation to SIL grade or type of excision. 'SF36v2 Mental Component Summary Score' and 'being parous and interested in fertility' were independent predictors of disease-specific FACIT-CD score. Impact Statement: What is already known on this subject? Long-term consequences of excisional treatments for cervical dysplasia on health-related quality of life (HRQoL) are not well reported. What do the results of this study add? Our study provides data on HRQoL in women treated with large loop excision of the transformation zone (LLETZ) or cold knife conization (CKC) obtained during the longest (median 5 years) follow-up as reported to date. We were able to show that having children and planning further pregnancies positively influenced HRQoL in these patients. In addition, we identified nulliparas with pregnancy desire as psychologically the most vulnerable group within the studied cohort. What are the implications of these findings for clinical practice and/or further research? Even several years after LLETZ or CKC, women may suffer from impaired Emotional Well-Being and reduced HRQoL. Awareness and assessment of these long-term consequences should be part of surveillance after excisional treatments for cervical dysplasia.